2023
DOI: 10.1029/2023gc011037
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Source Classification of Large Tephra Producing Eruptions Using Supervised Machine Learning: An Example From the Alaska‐Aleutian Arc

Jordan Lubbers,
Matthew Loewen,
Kristi Wallace
et al.

Abstract: Alaska contains over 130 volcanoes and volcanic fields that have been active within the last 2 million years. Of these, roughly 90 have erupted during the Holocene, with many characterized by at least one large explosive eruption. These large tephra‐producing eruptions (LTPEs) generate orders of magnitude more erupted material than a “typical” arc explosive eruption and distribute ash thousands of kilometers from their source. Because LTPEs occur infrequently, and the proximal explosive deposit record in Alask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, thanks to community databases, humans and machines can access large amounts of data effectively through the Findable, Accessible, Interoperable, and Reusable principle (Chamberlain et al, 2021;Farrell et al, 2021;Goldstein et al, 2014;Klöcking et al, 2023;Lehnert et al, 2000). Under these circumstances, geochemical data mining has become a practical approach for elucidating the processes occurring on Earth's surface and within its interior, at present and throughout geological history, such as tephrachronology and tephra studies (Bolton et al, 2020;Lubbers et al, 2023), hydrological studies (Shaughnessy et al, 2021;Wen et al, 2021), magmatic processes (Boschetty et al, 2022;Cortés et al, 2007;Costa et al, 2023;Keller et al, 2015), thermobarometry (Higgins et al, 2022;Jorgenson et al, 2022;Petrelli et al, 2020), tectonic distrimiantion (Doucet et al, 2022;Petrelli & Perugini, 2016;Ueki et al, 2018), sedimentary composition reflecting crust composition over time (Lipp et al, 2021;Ptáček et al, 2020), and long-term secular cooling of the mantle (Keller & Schoene, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thanks to community databases, humans and machines can access large amounts of data effectively through the Findable, Accessible, Interoperable, and Reusable principle (Chamberlain et al, 2021;Farrell et al, 2021;Goldstein et al, 2014;Klöcking et al, 2023;Lehnert et al, 2000). Under these circumstances, geochemical data mining has become a practical approach for elucidating the processes occurring on Earth's surface and within its interior, at present and throughout geological history, such as tephrachronology and tephra studies (Bolton et al, 2020;Lubbers et al, 2023), hydrological studies (Shaughnessy et al, 2021;Wen et al, 2021), magmatic processes (Boschetty et al, 2022;Cortés et al, 2007;Costa et al, 2023;Keller et al, 2015), thermobarometry (Higgins et al, 2022;Jorgenson et al, 2022;Petrelli et al, 2020), tectonic distrimiantion (Doucet et al, 2022;Petrelli & Perugini, 2016;Ueki et al, 2018), sedimentary composition reflecting crust composition over time (Lipp et al, 2021;Ptáček et al, 2020), and long-term secular cooling of the mantle (Keller & Schoene, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…for at least the past 30 years (Lowe et al, 2017), however, in comparison, the use of coding is a relatively new and still uncommon method applied to cryptotephra studies (e.g., Lubbers, 2023). The use of statistics and coding is important as it can appropriately handle large quantities of data, and case studies have shown that PCA in particular can be used to differentiate between separate groups within sets of data (Figure 1-5; Peti et al, 2019).…”
Section: Use Of Statistics and Coding In Cryptotephra Detectionmentioning
confidence: 99%